Adapting the role of handheld echocardiography during the COVID-19 pandemic: A practical guide. (September 2021) - Naderi, Hafiz; Robinson, Shaun; Swaans, Martin J; Bual, Nina; Cheung, Wing-See; Reid, Laura; Shun-Shin, Matthew; Asaria, Perviz; Pabari, Punam; Cole, Graham; Kanaganayagam, Gajen S; Sutaria, Nilesh; et al.
The COVID-19 pandemic has altered our approach to inpatient echocardiography delivery. There is now a greater focus to address key clinical questions likely to make an immediate impact in management, particularly during the period of widespread infection. Handheld echocardiography (HHE) can be used as a first-line assessment tool, limiting scanning time and exposure to high viral load. This article describes a potential role for HHE during a pandemic. We propose a protocol with a reporting template for a focused core dataset necessary in delivering an acute echocardiography service in the setting of a highly contagious disease, minimising risk to the operator. We cover the scenarios typically encountered in the acute cardiology setting and how an expert trained echocardiography team can identify such pathologies using a limited imaging format and include cardiac presentations encountered in those patients acutely unwell with COVID-19.